Novel insights into the quality changes and metabolite transfer rules of pickles during fermentation: Pickle versus pickle solution - Yanan Xia; Wenjing Zhu; Yufan Su; Yongfu Chen (Food Chemistry: X)
The key metabolites and control targets involved during fermentation of pickle need to be identified to improve its quality. This study aims to explore the changes in the quality of white radish during fermentation and the formation rules of key and harmful metabolites in pickle and pickle solutions. Results showed that the flavor profile of the pickle became more complex during fermentation. After fermentation of the pickle solution, metabolites such as D-tartaric acid and mannitol were significantly up-regulated, and the metabolism of nucleotides, histidine and riboflavin was active. Additionally, metabolites in pickle such as ginnalin B and Gly-Asn-Phe were notably up-regulated, and nucleotide metabolism and phenylalanine metabolism were active. 32 metabolites from the pickle were found to dissolve into the pickle solution, and 18 metabolites in the pickle solution penetrated into the pickle, in order to provide the theoretical basis for the quality control and industrial development of low-salt pickle.